The Impact of Board Gender Diversity and Audit Committee Meetings on Earnings Management: The Moderating Role of External Audit Quality - Eka Aulia Yustina; Muh. Syahru Ramadhan; Syafruddin Syafruddin (Advances in Taxation Research, 2026)
Purpose: This study examines the impact of board gender diversity and audit committee meetings on earnings management, and tests the moderating role of external audit quality. Research Method: Utilizing a causal-explanatory design and panel data regression, 606 observations were extracted from manufacturing companies listed on the Indonesia Stock Exchange (2021–2025) selected via purposive sampling. Results and Discussion: Empirically, board gender diversity and audit committee meetings positively affect earnings management, indicating tokenism and ceremonial compliance. However, Big Four external auditors significantly moderate this relationship by weakening these dysfunctional internal mechanisms, acting as an effective last line of defense. Implications: Regulators must shift from enforcing structural demographic quotas to empowering substantive oversight. Investors should prioritize firms audited by reputable auditors. Future research is encouraged to expand across diverse sectors using multidimensional metrics. Originality: This study uniquely integrates Resource Dependence Theory and Agency Theory, demonstrating that internal governance in emerging markets cannot operate in isolation and strictly requires synergy with high-quality external audits.